Impairment of gastric accommodation induced by water‐avoidance stress is mediated by 5‐HT2B receptors. Issue 5 (2nd February 2016) - Miwa, H.; Koseki, J.; Oshima, T.; Hattori, T.; Kase, Y.; Kondo, T.; Fukui, H.; Tomita, T.; Ohda, Y.; Watari, J.
Abstract: Background: Psychological stress has been shown to impair gastric accommodation (GA), but its mechanism has not been elucidated. This study was conducted to clarify the role of 5‐HT2B receptors in a guinea pig model of stress‐induced impairment of GA. Methods: Gastric accommodation was evaluated by measuring the intrabag pressure in the proximal stomach after administration of a liquid meal. The guinea pigs were subjected to water‐avoidance stress. The role of 5‐HT2B receptors in impairment of GA was investigated by administering a 5‐HT2B receptor agonist (BW723C86) or antagonist (SB215505), the traditional Japanese medicine rikkunshito (RKT), a muscarinic M3 receptor antagonist (1, 1‐dimethyl‐4‐diphenylacetoxypiperidium iodide [4‐DAMP]), or a nitric oxide synthase inhibitor (N ω ‐nitro‐L‐arginine [L‐NNA]). Key Results: In normal animals, liquid meal‐induced GA was inhibited by BW723C86, but was not affected by SB215505. The inhibition of GA by BW723C86 was reversed by co‐administration of 4‐DAMP. Compared to normal animals, GA in stressed animals was significantly inhibited. SB215505 and RKT significantly suppressed stress‐induced impairment of GA. After meal administration, the level of cyclic guanosine monophosphate in gastric fundus tissue increased by approximately twofold in normal animals, but did not change in stressed animals. The inhibition of GA by L‐NNA was suppressed by SB215505 or RKT. At a dose that did not affect GA in normal animals, BW723C86 exacerbated the impairment of GA in stressed animals. Conclusions and Inferences: Stress‐induced impairment of GA may be mediated by an increased responsiveness of 5‐HT2B receptors, and activation of the 5‐HT2B receptor signaling pathway may have an inhibitory effect on nitric oxide function. Abstract : Water‐avoidance stress significantly inhibited liquid meal‐induced gastric accommodation; this inhibition was reversed by 5‐HT2B receptor antagonist. This result suggests that stress‐induced impairment of gastric accommodation is mediated by the activation of 5‐HT2B receptors.